2019
DOI: 10.1017/xps.2019.28
|View full text |Cite
|
Sign up to set email alerts
|

Does Process Matter? Direct Democracy and Citizens’ Perceptions of Laws

Abstract: Does the process used to pass a law affect the way citizens evaluate the outcome? In a series of experiments, I manipulate the way in which a law is passed – ballot initiative or the legislative process – to test the effect of process on citizens’ evaluations of policy outcomes. The results show that people view the ballot initiative process as fairer than the legislative process, but that process has a negligible effect on outcome evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…There is growing evidence that citizens’ support for decision-making procedures such as referenda flips depending on their chance of achieving a favorable outcome (Werner, 2020). Moreover, perceived fairness of democratic procedures for decision-making has either negligible effect on the evaluation of adopted policies (Ladam, 2019) or might be context-specific and pertinent under particular conditions (e.g., government crisis response, see Mazepus & van Leeuwen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that citizens’ support for decision-making procedures such as referenda flips depending on their chance of achieving a favorable outcome (Werner, 2020). Moreover, perceived fairness of democratic procedures for decision-making has either negligible effect on the evaluation of adopted policies (Ladam, 2019) or might be context-specific and pertinent under particular conditions (e.g., government crisis response, see Mazepus & van Leeuwen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…If we are concerned with estimating the latent associated traits of attention (such as age, education), it should actually be easier and more informative when our measure of attention comes from an open-rather than closed-ended manipulation check. For example, I brie y checked the percent of respondents that correctly answered factual closed-ended manipulation checks in some recent political science publications and found that it was typically above 90%, which does not really distinguish attention between participants though it likely exists(Edwards and Arnon 2019;Keiser and Miller 2020;Jamieson and Weller 2019;Kim and Kweon 2020;Ladam 2019). If there is very little variation in our measure of attention, as is the case when over 90% of respondents correctly answer a closed-ended manipulation check, socio-demographic variables do not have any variation to explain.…”
mentioning
confidence: 99%